Site‐Specific Oxidation‐Induced Stiffening and Shape Morphing of Soft Tough Hydrogels. Issue 3 (12th December 2018) - Wang, Jiahui; Li, Tianzhen; Chen, Fan; Zhou, Dan; Gan, Tiansheng; Zhou, Xiaohu; Handschuh‐Wang, Stephan; Zhao, Liqing; Zhou, Xuechang
Abstract: Living biological tissues are made of structures with properly defined mechanical properties (toughness and stiffness) toward specific biological functions. Herein, a chemical manipulation strategy is developed to locally vary the oxidation state of Fe ions from divalent to trivalent in the tough hydrogels. The resultant trivalent ionically cross‐linked networks become less flexible and lead to a significant enhancement of the stiffness of the tough hydrogels. The mechanical strengthening of Fe 2+ /Ca 2+ ‐alginate/polyacrylamide tough hydrogels is demonstrated by the oxidation with ammonium persulfate (APS). Moreover, by applying surface patterning, the mechanical properties of the tough hydrogels are spatially stiffened and thus can serve as anisotropic elements to guide the shape morphing of tough hydrogels into complex 3D structures. This method opens up a simple strategy not only to dynamically vary the mechanics of tough hydrogels, both in bulk and locally from prefabricated soft tough hydrogels, but also toward their shape morphing behaviors on demand. Abstract : Stiffening and shape morphing of soft Fe 2+ /Ca 2+ ‐alginate/polyacrylamide tough hydrogels is achieved by applying a chemical manipulation method to localized varying the oxidation state of Fe ions from divalent to trivalent. With this method, 3D molding or shape morphing of tough hydrogels is realized by the as‐encoded mechanical anisotropy.